Gasoline, Ethanol and Methanol (GEM) Ternary Blends utilization as an Alternative to Conventional Iraqi Gasoline to Suppress Emitted Sulfur and Lead Components to Environment - Chaichan, Miqdam Tariq (Al-Khwarizmi Engineering Journal, 2017)
Iraqi conventional gasoline characterized by its low octane number not exceed 82 and high lead and sulfur content. In this paper tri-component or ternary, blends of gasoline, ethanol, and methanol presented as an alternative fuel for Iraqi conventional gasoline. The study conducted by using GEM blend that equals E85 blend in octane rating. The used GEM selected from Turner, 2010 collection. G37 E20 M43 (37% gasoline + 20% ethanol+ 43% methanol) was chosen as GEM in present study. This blend used in multi-cylinder Mercedes engine, and the engine performance, and emitted emissions compared with that produced by a gasoline engine.The results show that this blend can formulate with available Iraqi produced materials. GEM ternary blend offers significant advantages in terms of engine performance compared to gasoline. Also, GEM higher useful compression ratio (HUCR) = 9.25 while gasoline HUCR=7.5. The increment in engine bp was 24.12%, BSFC reduced by 13.9% and brake thermal efficiency increased by 19.59%. The volumetric efficiency increased by 8.06%. Also, CO, HC concentrations were reduced by 30.5%, 25.16% respectively. Smoke opacity reduced by 46.49% and CO2 concentrations reduced by 5% as well as NOx concentrations that reduced by 1.75%.